2018
DOI: 10.3758/s13428-018-1065-0
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of touchscreens for testing primate food preferences and valuations

Abstract: Typically, animals' food preferences are tested manually, which can be both time-consuming and vulnerable to experimenter biases. Given the utility of ascertaining animals' food preferences for research and husbandry protocols, developing a quick, reliable, and flexible paradigm would be valuable for expediting many research protocols. Therefore, we evaluated the efficacy of using a touchscreen interface to test nonhuman primates' food preferences and valuations, adapting previously validated manual methods. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 60 publications
2
54
0
Order By: Relevance
“…; Micheletta, Whitehouse, Parr, & Waller, ; Waller, Peirce, Mitchell, & Micheletta, ; Whitehouse et al, , ). There has also been growth in more applied science in zoos using touchscreens, with researchers exploring welfare implications of cognitive testing (Tarou et al, ; Wagner et al, ), preferences (Hopper et al, in press; Perdue, ), personality (Altschul, Wallace, Sonnweber, Tomonaga, & Weiss, ), and mood (Allritz et al, ; Cronin et al, ; Kret, Jaasma, Bionda, & Wijnen, ) in several species.…”
Section: The History and Current Setting Of Zoo‐based Touchscreen Resmentioning
confidence: 99%
See 2 more Smart Citations
“…; Micheletta, Whitehouse, Parr, & Waller, ; Waller, Peirce, Mitchell, & Micheletta, ; Whitehouse et al, , ). There has also been growth in more applied science in zoos using touchscreens, with researchers exploring welfare implications of cognitive testing (Tarou et al, ; Wagner et al, ), preferences (Hopper et al, in press; Perdue, ), personality (Altschul, Wallace, Sonnweber, Tomonaga, & Weiss, ), and mood (Allritz et al, ; Cronin et al, ; Kret, Jaasma, Bionda, & Wijnen, ) in several species.…”
Section: The History and Current Setting Of Zoo‐based Touchscreen Resmentioning
confidence: 99%
“…Alternatively, researchers can collaborate with experienced software developers to create a program that meets their needs (Hopper et al, in press; Martin, ). Consideration should be given to the degree to which third‐party developers will be available to maintain the program as operating systems are updated over time, and the cost of purchasing tailor‐made software, or even off‐the counter software.…”
Section: Logistical Considerations Of Zoo‐based Touchscreen Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer touchscreen systems can also help to evaluate other forms of enrichment; McGuire et al (2017) recently employed a computer touchscreen system to measure the effect of browse presence on gorilla cognitive bias or “mood” (i.e., to evaluate browse as a form of enrichment). Hopper et al (2018) used a computer touchscreen to assess food preferences in a single zoo gorilla, which could then inform which foods were used as rewards for this individual in future enrichment. Touchscreen systems can be extremely beneficial to enrichment efforts, because subjects’ responses to virtual (on-screen) stimuli can be logged automatically, and many digital stimulus combinations can be provided without the need for cumbersome or expensive physical apparatus (Cronin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral research of captive animal food preferences have detailed how to choose effective reinforcers to improve training efficacy, husbandry and animal welfare [17]. Specifically, nonhuman primate researchers have experimentally determined primate food valuation and showed that the use of preferred foods increases engagement during training sessions [18, 19]. In this study, preferred foods were determined based on caregiver observations of increased consumption, and these foods were used as reinforcers during PRT.…”
Section: Introductionmentioning
confidence: 99%